1993
DOI: 10.2307/1170558
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anomalous Data in Knowledge Acquisition: A Theoretical Framework and Implications for Science Instruction

Abstract: Understanding how science students respond to anomalous data is essential to understanding knowledge acquisition in science classrooms. In this report, we present a detailed analysis of the ways in which scientists and science students respond to anomalous data. We postulate that there are seven distinct forms of response to anomalous data, only one of which is to accept the data and change theories. The other six responses involve discounting the data in various ways in order to protect the preinstructional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
420
1
35

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(485 citation statements)
references
References 37 publications
15
420
1
35
Order By: Relevance
“…This is consistent with intuitive application of fuzzy logic (e.g., Zazkis 1995) to a mathematical situation. Further, prime numbers were the most notable exceptions from the perceived 'rule', which is in accord with Chinn and Brewer (1993) category of "excluding data from the currently held theory", as is exemplified below.…”
Section: Who Is Right?mentioning
confidence: 74%
See 3 more Smart Citations
“…This is consistent with intuitive application of fuzzy logic (e.g., Zazkis 1995) to a mathematical situation. Further, prime numbers were the most notable exceptions from the perceived 'rule', which is in accord with Chinn and Brewer (1993) category of "excluding data from the currently held theory", as is exemplified below.…”
Section: Who Is Right?mentioning
confidence: 74%
“…Clyde: I wasn't sure myself either, I just didn't want you to think you were right so I denied it. Students' tendency to reject evidence that is not in accord with their held beliefs was noted in several studies (e.g., Chinn and Brewer 1993;Edwards 1997). Given that script-writers were prospective teachers, this tendency of their script characters exemplifies their awareness of such behavior among students.…”
Section: Prime Numbers As Exceptionsmentioning
confidence: 90%
See 2 more Smart Citations
“…While an appropriate response would be to evaluate the alignment between experimental findings and hypotheses, reflect on causes, and make necessary adjustments, Chinn and Brewer (1993) found that learners would discount anomalous data in various ways to defend their original theory. Researchers have linked such behaviors to learners' epistemic beliefs (e.g., Pintrinch, Marx, & Boyle, 1993;Qian & Alverman, 1995;Windschitl & Andre, 1998).…”
Section: The Role Of Motivation and Beliefsmentioning
confidence: 99%